Superior electrochemical water oxidation of novel NiS@FeS2 nanocomposites. (October 2019) - Jansi Rani, B.; Aiswarya Kanjana, P.; Ravi, G.; Yuvakkumar, R.; Saravanakumar, B.
Abstract: NiS, FeS2 and NiS@FeS2 nanocomposites were optimally synthesized by employing solvothermal method. Prepared nanocomposites were confirmed by X-ray diffraction spectra (XRD) by obtaining strong diffraction correspond to rhombohedral and orthorhombic phase of NiS and FeS2 respectively. A well defined Raman active mode of vibrations obtained around 337, 477 and 543 cm −1 revealed for NiS@FeS2 nanocomposites. Metal sulphide vibrations such as Ni–S and Fe–S were confirmed by Fourier transform infrared spectra (FTIR). The morphological determination and the tiny particles combination was revealed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) studies. The superior performance of NiS@FeS2 nanocomposites towards electrochemical water oxidation has been observed from cyclic voltammogram (CV) and linear sweep volttammogram (LSV) results. The higher current density of 399 mA/g was achieved for the optimized NiS@FeS2 nanocomposites at 10 mV/s scan rate with very low Tafel slope value of 63 mV/dec. Furthermore, 12 h of long lasting stability around 120% was achieved for the same electrode for superior electrochemical water oxidation. The observed results strongly recommended that the controlled synthesis of NiS@FeS2 nanocomposites coated Ni foam substrate could be acted as an efficient working electrode for superior water oxidation process for sustainable electrochemical water splitting potential applications. Graphical abstract: Image 1 Highlights: Novel NiS@FeS2 was synthesized by solvothermal process. Remarkable OER activity of NiS@FeS2 nanocomposite electrode was achieved. 399 mA/g at 10 mV/s scan rate with lower overpotential of 298 mV. 120% efficiency achieved for NiS@FeS2 after 12 h. Superiorly performed NiS@FeS2 electrode was fabricated.